Long term endocrine issues in adults born prematurely: a systematic review - Claffey, T.; Cullinan, A.; Downey, J.; Haupfear, I.; Kilbride, A.; May, E.; Murchan, E.; Prendiville, K.; Sullivan, M.; Trayer, J.; Stewart, P.; Branagan, A.; et al. (Frontiers in Pediatrics, 2025)
BackgroundPrematurity is a risk factor for chronic disease later in life. According to figures in Ireland, preterm births represent 7% of all births which presents a significant issue for adult healthcare resources. This systematic review synthesised the evidence on long-term endocrine related outcomes for adults who were born prematurely.MethodsA systematic review was conducted by searching the official databases PubMed and Web of Science. Studies were included in the review based on the criteria that they investigated an endocrine outcome in adulthood in the following categories: issues of the hypothalamic-pituitary axis, growth, thyroid, adrenal function, insulin sensitivity, lipid metabolism, cardiometabolic pathology, and bone health. We were guided by the standards set by the “Preferred Reporting Items for Systematic Review and Meta-Analysis” (PRISMA) Statement.ResultsThe search yielded 1,814 studies and after removal of duplicates, 1,584 papers entered screening. 65 full texts were reviewed, after inclusion and exclusion criteria was applied, 27 studies were used for data extraction. Results revealed that being born premature was a significant risk factor for a myriad of endocrine issues in later life. Reduced height, dysfunction of the HPA axis, lower fertility rates, lower bone mineral density and increased odds of hypothyroidism were all outcomes that were associated with preterm birth. Cardiometabolic related outcomes formed the bulk of our data (11/27); these studies found associations between prematurity and increased risk of diabetes, decreased insulin sensitivity, higher body fat percentage and dyslipidaemia.DiscussionThis review highlighted that prematurity is associated with long term endocrine dysfunction in multiple domains. It provided a large set of data demonstrating this association across the various endocrine pathologies relating to bone, thyroid, growth, reproduction and metabolism. This highlights the necessity of long term follow up into adulthood for individuals born preterm.